Thrombo-Inflammation and Immunological Response in Ischemic Stroke: Focusing on Platelet-Tregs Interaction - Cui, Jieqiong; Li, Huayan; Chen, Zongning; Dong, Ting; He, Xiying; Wei, Yuanyuan; Li, Zhengkun; Duan, Jinfeng; Cao, Ting; Chen, Qian; Ma, Dongmei; Zhou, Yang; et al. (Frontiers in Cellular Neuroscience, 2022)
Strokes are mainly caused by thromboembolic obstruction of a major cerebral artery. Major clinical manifestations include paralysis hemiplegia, aphasia, memory, and learning disorders. In the case of ischemic stroke (IS), hyperactive platelets contribute to advancing an acute thrombotic event progression. Therefore, the principal goal of treatment is to recanalize the occluded vessel and restore cerebral blood flow by thrombolysis or mechanical thrombectomy. However, antiplatelets or thrombolytic therapy may increase the risk of bleeding. Beyond the involvement in thrombosis, platelets also contribute to the inflammatory process induced by cerebral ischemia. Platelet-mediated thrombosis and inflammation in IS lie primarily in the interaction of platelet receptors with endothelial cells and immune cells, including T-cells, monocytes/macrophages, and neutrophils. Following revascularization, intervention with conventional antiplatelet medicines such as aspirin or clopidogrel does not substantially diminish infarct development, most likely due to the limited effects on the thrombo-inflammation process. Emerging evidence has shown that T cells, especially regulatory T cells (Tregs), maintain immune homeostasis and suppress immune responses, playing a critical immunomodulatory role in ischemia-reperfusion injury. Hence, considering the deleterious effects of inflammatory and immune responses, there is an urgent need for more targeted agents to limit the thrombotic-inflammatory activity of platelets and minimize the risk of a cerebral hemorrhage. This review highlights the involvement of platelets in neuroinﬂammation and the evolving role of Tregs and platelets in IS. In response to all issues, preclinical and clinical strategies should generate more viable therapeutics for preventing and managing IS with immunotherapy targeting platelets and Tregs.